2015
DOI: 10.3174/ajnr.a4556
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Alterations in Community Dwelling Individuals with Chronic Joint Pain

Abstract: BACKGROUND AND PURPOSE:Central sensitization in chronic pain involves structural brain changes that influence vulnerability to pain. Identifying brain regions involved in pain processing and sensitization can provide more insight into chronic pain. This study examines structural brain changes in chronic pain and experimental pain in a large population-based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…Previous studies have indicated that chronic pain can induce volume changes in the brain (May, 2008; Kregel et al, 2015; de Kruijf et al, 2016). The brain gray matter is closely associated with the body’s pain perception (Cauda et al, 2014; Emerson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that chronic pain can induce volume changes in the brain (May, 2008; Kregel et al, 2015; de Kruijf et al, 2016). The brain gray matter is closely associated with the body’s pain perception (Cauda et al, 2014; Emerson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, two-third of the subjects with daily chronic pain were females; comorbid daily chronic pain and chronic cough were also more prevalent in females. DE KRUIJF et al [30] found that females with chronic pain have smaller total gray matter volume suggesting sex-specific changes in the brain in response to chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Grey matter volume of the temporal and frontal lobes and the hippocampus were found to be smaller in women with pain compared to those without pain, indicated involvement of emotional processing. The volumetric differences found indicated a sex-specific neuroplasticity in chronic pain [ 211 ]. Lower sex hormone levels were found to be associated with chronic musculoskeletal pain, independent from lifestyle and health-related factors in women, suggesting that sex hormones play a role in chronic pain and should be taken into account when a patient presents with chronic pain [ 212 ].…”
Section: Locomotor Diseasesmentioning
confidence: 99%